Diyarbakır Hasan Pasha Inn: A thorough evaluation of risk analysis and accessibility concerns - Barış, Barış; Müezzinoğlu, Menşure Kübra (My University, 2024)
The importance of accessibility in maintaining historical and cultural structures is evident across all facets of society. It is crucial to ensure that these structures remain secure, readily available, and sustainable, as they represent significant cultural heritage for both the local community and tourists. In this study, the risk analysis and accessibility status of the historic Hasan Pasha Inn in Diyarbakır’s Sur district were thoroughly explored. The Inn holds a significant historical and cultural location on Gazi Street, across from the Ulu Mosque. The primary goals of the research are to identify current risks, conduct a methodical analysis, and offer suggestions for risk mitigation. The Inn’s accessibility was assessed by aligning headings with the accessibility guide. The analysis utilized the 5x5 L-type matrix method to systematically evaluate risks based on specific criteria and determine their relative importance. Risk factors were categorized as minor (0–6), medium (8–12), major (16–20), and disaster (25 and above). A total of 31 risks were identified and grouped under different headings. Precautions were suggested for each risk with the goal of reducing the Inn’s overall risk levels. Measures such as improving physical access, enhancing emergency preparedness, implementing safety measures, and undertaking maintenance and repair projects are being pursued to promote tourism and enhance safety in the neighborhood for both locals and visitors. The study concludes by outlining the necessary actions to improve accessibility and safety at the Hasan Pasha Inn, while also contributing to the preservation of this historic building. The proposed measures aim to make the Inn more accessible to both locals and tourists, and to ensure the sustainability of this culturally significant site. The findings of the study will serve as a valuable resource for enhancing accessibility standards and conserving historic buildings. The limited number of publications on accessibility in historical buildings reveals the need to raise awareness in this field and offer solution suggestions; Therefore, the work we carry out is of great importance. It is expected that this study will offer insights for future risk analyses and accessibility evaluations of similar structures.
Keywords: Risk analysis; cultural heritage; risk assessment; accessibility; Diyarbakır Hasan Pasha Inn